The Relationship between Human Capital, Relational Capital and Capital Structure in Encouraging Business Performance: A Study in Creative Industry of Batik Trusmi, Cirebon District, West Java, Indonesia - Sutisna, Deden; Haizam Bin Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to test the level of relationship between human capital and relational capital and structure capital and business performance that develops the Batik creative industry in Trusmi in Cirebon District, West Java. The research respondents regarding business and workers in this industry sector amounted to 10 creative industries with 10 employees each. The research method is a survey, primary data sources with questionnaires, interviews, and observations as a data collection tool on the object of analysis. Test data using the validity, reliability, and classical assumptions test with product moment assessment analysis tools and determination. The results of the study indicate that the level of the relationship between 1) human capital and low category capital structure, 2) human capital and financial performance are very low, 3) human capital and financial performance are very low, 4) human capital and optional capital are strong categories, 5) working capital and capital structure are very low, 6) relational capital and very low financial performance, 7) relational capital and very low financial performance, and 8) capital structure and business performance are very low. Being able to separate from the levels built by dominant variables gives a low influence, except between Capita Humans and Relational Capital giving strong ones.